Artificial Neural Network Based Prediction Of Electrical Test Parameters In Wafer Fabrication Technology - Ke, Joseph Kian Seng (2005)
In semiconductor industry, cycle time of the wafer fabrication is very crucial and one of the contributing factors comes from wafer testing. This thesis presents the application of back propagation Artificial Neural Network (ANN) model designed to infer electrical test parameters from the given list of parameters with the intention of reducing test time, to enhance throughput, and to improve cycle time.